Binding of safranal to whey proteins in aqueous solution: Combination of headspace solid-phase microextraction/gas chromatography with multi spectroscopic techniques and docking studies. (30th July 2019) - Feyzi, Samira; Varidi, Mehdi; Housaindokht, Mohammad Reza; Es'haghi, Zarrin
Highlights: Binding of safranal to whey proteins was confirmed by HS–SPME–GC and spectroscopic approaches. Bovine serum albumin showed the highest affinity toward safranal. Safranal binding resulted in tertiary structural changes of whey proteins. Safranal complexation caused more ordered secondary structure in whey proteins. Abstract: The objective of this work was to study molecular binding of safranal to whey proteins by taking advantage of headspace solid-phase microextraction combined with gas chromatography (HS–SPME/GC), fluorescence and circular dichroism (CD) spectroscopies, and docking studies. The results of HS-SPME/GC indicated that bovine serum albumin (BSA) had the highest affinity toward safranal, with binding constant of 3.196 × 10 3  M −1 . Also, binding strength was reduced in the order of α-lactalbumin (α-Lact), whey protein isolate (WPI), and β-lactoglobulin (β-Lg). Although there was a good agreement between results of HS–SPME/GC and fluorescence spectroscopy regarding the safranal binding site on whey proteins, the order of their binding affinity toward safranal was not consistent for both techniques. According to docking studies, conformational alterations in secondary and tertiary structures of whey proteins induced by safranal association resulted from hydrophobic interactions and hydrogen bonds.